THE ROLE OF THE FREE-ACTIVE PRINCIPLE AS THE FOUNDATION OF INDONESIA FOREIGN POLICY IN THE STRATEGY OF CULTURAL DIPLOMACY - Muhammad Zudi Hardiansyah; Wawan Sopian; Ramma Firdaus (Khazanah: Jurnal Mahasiswa, 2021)
Background: The principle of free-active principle is the basis of Indonesia's foreign policy. Free means that Indonesia may determine attitudes and decisions regarding the conditions and circumstances being experienced without the influence of other parties. Active means that Indonesia is not only an object in the international world, but a subject who is actively involved in helping to implement world peace. The purpose of this article is to explain the relationship between the principle free-active with cultural diplomacy, and also to prove the implementation of the principle of free-active in cultural diplomacy that has been carried out by Indonesia. Method: Qualitative. For data-collections, the technique that are used are free listening speaking techniques and note-taking techniques. For data-analysis, the techniques that are used are data reduction, data presentation, and conclusion drawing Result: To explain the birth of the principle free-active in Indonesia, the principle of freeactive as the foundation of Indonesia's foreign policy, the relationship of cultural diplomacy and the principle of free-active, and the analysis of the phenomenon of cultural diplomacy based on the principle of free-active. Conclusion: The principle of free-active was born when Indonesia was still in the form of RIS. This principle has been implemented by Indonesia until now with concrete evidence of the establishment of the KAA, the preservation of Betutu Chicken as a Balinese culinary, up to the creation of the Indonesian Cultural House in Germany. Keywords: Free-active, cultural diplomacy, Indonesia, foreign policy